Synthesis and characterization of poly(1,2,3-triazole)s with inherent high sulfur content for optical applications - Mazumder, Kajari; Komber, Hartmut; Bittrich, Eva; Voit, Brigitte; Banerjee, Susanta (Journal of Polymer Science, 2023)
The synthesis of solution-processable sulfur-containing polytriazoles for optoelectronic applications is a relatively less explored domain in polymer research. The synthesis of novel bifunctional (DA) and trifunctional (TA) azido-monomers with inherent high sulfur content and of organo-soluble high refractive index poly(1,2,3-triazole)s using the azido-monomers via Cu(I) assisted click polymerization reactions are reported in this work. The azido-monomers were synthesized by the conversion of previously reported amine-functionalized compounds to azides using azidotrimethylsilane in a polar aprotic solvent. Dialkyne monomers were also synthesized and reacted with the azides to prepare a series of five linear and two hyperbranched poly(1,2,3-triazole)s. Fourier transform infrared spectroscopy, nuclear magnetic resonance spectroscopy, differential scanning calorimetry and thermogravimetric analysis were used to characterize the synthesized polymers. It was also demonstrated that the use of the trifunctional azide in optimized conditions resulted in increased solubility of an otherwise insoluble linear poly(1,2,3-triazole). The optical characterization of the polymers was carried out on thin polymer films with thickness in the nanometer range, which were successfully prepared by spin-coating on silicon wafers. It was found that the increase in the sulfur and aromatic content in the polymer backbone successfully increased the refractive index of the polymers up to 1.743 at 589 nm.
CRIS-Team Scopus Importer:2023-03-20
Keywords: birefringence; click polymerization; high refractive index; optical properties of poly(1; 2; 3-triazole)s; sulfur containing poly(1; 2; 3-triazole)s